A new fuzzy rule based transition algorithm between flux models for speed sensorless vector controlled induction motor drives at low speed region - Akin, E; Karaköse, M (Taylor & Francis Inc, 2005)
This article proposes a fuzzy logic based smooth transition method between flux models for a stator flux oriented induction motor drive. The major task of the fuzzy logic based transition algorithm is to eliminate torque jerk during the transition between the flux estimation models. Since the voltage model cannot be used at low speed operations, and the current model needs speed sensor two flux models are used together for flux estimation. The drive using the current model and the voltage model together can be smoothly started up by using fuzzy rule based transition algorithm. Proposed algorithm was simulated by MATLAB/SIMULINK and simulation results were verified by experimental ones, obtained via 32-bit DS1102 controller board based drive setup. Fuzzy logic transition based vector controlled induction motor was operated at transition speed region and motor was stable. Without using any other mathematical models, the performance of the transition algorithm is found satisfactory.
Keywords: current model; fuzzy transition; induction motor; vector control; voltage model